2016
DOI: 10.3847/2041-8205/827/2/l34
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational-Wave Observations May Constrain Gamma-Ray Burst Models: The Case of Gw150914–gbm

Abstract: The possible short gamma-ray burst (GRB) observed by Fermi/GBM in coincidence with the first gravitationalwave (GW) detection offers new ways to test GRB prompt emission models. GW observations provide previously inaccessible physical parameters for the black hole central engine such as its horizon radius and rotation parameter. Using a minimum jet launching radius from the Advanced LIGO measurement of GW150914, we calculate photospheric and internal shock models and find that they are marginally inconsistent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…Lyutikov (2016) has argued that the physical properties necessary to create GW150914-GBM are highly implausible, although Khan et al (2018) surveyed different models of disks around merging BBHs using magnetohydrodynamic simulations and shows that such systems could produce an EM counterpart consistent with the properties of GW150914-GBM. Likewise Veres et al (2016) showed that dissipative photosphere models of GRB emission can accommodate the GBM observations. Ultimately, the detection of another EM signal from a BBH system will be required to conclusively settle the debate as to the origin of GW150914-GBM.…”
Section: Discussionmentioning
confidence: 94%
“…Lyutikov (2016) has argued that the physical properties necessary to create GW150914-GBM are highly implausible, although Khan et al (2018) surveyed different models of disks around merging BBHs using magnetohydrodynamic simulations and shows that such systems could produce an EM counterpart consistent with the properties of GW150914-GBM. Likewise Veres et al (2016) showed that dissipative photosphere models of GRB emission can accommodate the GBM observations. Ultimately, the detection of another EM signal from a BBH system will be required to conclusively settle the debate as to the origin of GW150914-GBM.…”
Section: Discussionmentioning
confidence: 94%
“…In light of a new study by Veres et al (2016), where a CPL was fit to the 14 detector GBM data to understand the plausible physical GRB scenarios that could explain the signal, we reexamine the spectral models of the GBM event. The authors use a method, which is not described, to incorporate multiple locations along the LIGO arc and Monte Carlo the maximum likelihood profile of the parameters.…”
Section: Comment On the Case Of Gw150914-gbm Eventmentioning
confidence: 99%
“…According to Perna et al (2016), an sGRB might result from the BBH merger triggering the accretion of a disk around one of the BHs in the final seconds before the coalescence, but Kimura et al (2017) find it is difficult to have the disk survive down to seconds before the coalescence as required. An efficient way to power EM emission is the Blandford-Znajek (Blandford & Znajek 1977) process of electromagnetic extraction of mechanical energy (Li et al 2016;Veres et al 2016). Lyutikov (2016), however, pointed out that the EM luminosity associated with GW150914 would require magnetic fields of ∼10 12 G, astrophysically implausible for an environment around a BH.…”
Section: Discussionmentioning
confidence: 99%